Mushrooms of the Southeastern United States - Bessette, Alan (Syracuse University Press, 2015)
This book is a comprehensive field guide to the mushrooms of the southeastern United States. Although it will stand on its own, it is intended to compliment and serve as a companion to Mushrooms of Northeastern North America, also published by Syracuse University Press. Together these volumes form a foundation and reference for identifying mushrooms found in eastern North America from Canada to the subtropics of Florida and Texas. This book features more than 450 species that are fully described and illustrated with photographs, many for the first time in color. The photographs were selected for high-quality color fidelity and documentary merit, and reflect some of the aesthetic appeal of our subject. The number of species described and illustrated in color is substantially more than has previously appeared in any other single work devoted to the mushrooms of the southeastern United States. Cross referencing to additional species occuring in the region that are illustrated in Mushrooms of Northeastern North America is provided. Although this book contains the necessary detail required by advanced students and professional mycologists, it emphasizes identification based primarily on macroscopic field characters for easier use by a general audience. Each illustrated species is accompanied by a detailed description of macroscopic and microscopic features based on the concepts of their original authors.